Short Term Outcome of Urethroplasty with or without Urethral Stent: A Comparative Study - Karim, SM Rezaul; Abdullah, Sheikh Md; Shaha, Bablu Kumar; Rahman, Md Matiur; Amin, Md Ruhul (Medicine Today, 2013)
Urethroplasty is the surgery for Hypospadias. The most common complication of Hypospadias surgery is urethro-cutaneous (U-C) fistula. We designed this study to compare the short term outcome of Urethroplasty with or without urethral stent postoperatively. A total 30 patients of distal penile hypospadias except glnular variety have been studied prospectively in Pediatric Surgery Department of Banga Bandhu Sheikh Mujib Medical University, Dhaka for a period of 20 months, from March 2005 to October 2006. All patients were divided into Group-A (pt with stent) and Group- B (pts without stent). Age ranges of all patients were 2-12 years. After operation no patient developed urinary retention in stented group (Group-A) and 3 patients developed urinary retention which was managed by suprapubic puncture. 5 patients developed urethra-cutaneous fistula in stented group (Group- A) and 2 patients developed fistula in non stented group (Group-B). Calibration was done in all patients after 2 weeks of operation. Before calibration 2 patients came to us with narrow urinary stream of Group-B. After analyzing the result, it was concluded that the short term outcome of Urethroplasty without postoperative urethral stent is better than with stent specially in terms of Urethro-cutaneous fistula. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14110 Medicine TODAY Vol.24(1) 2012 pp.23-26